Analisis Deskriptif Strategi Komunikasi Hotel Sakura Syariah - Nazwirman Nazwirman; Efendy Zein (Journal of Economics and Business Aseanomics (JEBA), 2020)
The research objective describes an integrated marketing communication strategy in developing Sakura Syariah Hotel to see a comprehensive marketing communication strategy. Hotel Sakura Syariah is a 3-star syariah concept hotel which has 70 rooms. The analytical method uses the 7P (marketing mix) approach. The research results to increase the number of guests staying the strategy consisted of products, which offer a sharia concept with various types of representative rooms. Pricing, using the appropriate price preferences. Place, hotel location that is close to the center of the district capital and easy access. Promotion, with direct selling in accordance with local government and private selling by participating in various marketing events, sales proposals and advertising. People, conduct trainings to improve human resource capabilities. Physical evidence, a physical building that has Sharia characters and is supported by fairly good technology. Process, reservation service is quite fast and excellent. The development of this Sayriah hotel must be supported by related parties, especially the local government in order to increase the number of hotel guests